1980
DOI: 10.1093/genetics/96.3.697
|View full text |Cite
|
Sign up to set email alerts
|

Linkage Relationships of 19 Enzyme Loci in Maize

Abstract: Linkage relationships of 19 enzyme loci have been examined. The chromosomal locations of eight of these loci are formally reported for the first time in this paper. These localizations should assist in the construction of additional useful chromosome marker stocks, especially since several of these enzyme loci lie in regions that were previously poorly mapped. Six loci are on the long arm of chromosome 1. The arrangement is (centromere)—Mdh4-mmm-Pgm1-Adh1-Phi-Gdh1, with about 46% recombination between Mdh4 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

1987
1987
2015
2015

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(4 citation statements)
references
References 0 publications
1
3
0
Order By: Relevance
“…Both loci appear to code for monomeric enzymes, as reported with other plants (9,14). PGM-1 has double-banded electromorphs, as observed in Camellia (28), maize (13), balsam fir (21), and cole crops (4). One electromorph has bands at the relative positions of 89 and 78, and the other at 78 and 70.…”
Section: Resultssupporting
confidence: 66%
See 1 more Smart Citation
“…Both loci appear to code for monomeric enzymes, as reported with other plants (9,14). PGM-1 has double-banded electromorphs, as observed in Camellia (28), maize (13), balsam fir (21), and cole crops (4). One electromorph has bands at the relative positions of 89 and 78, and the other at 78 and 70.…”
Section: Resultssupporting
confidence: 66%
“…Two virus source clones were used for inoculation, F. xananassa 'Totem' Puyallup clone 3 (FM5-3) and F. xananassa 'Totem' Mount Vernon clone (MV-1). Both clones were infected with a complex of mottle, mild yellow edge, and crinkle viruses (13). From 33 to 42 seedlings of each age were inoculated with each virus source, and 15 or 18 seedlings of each age were used as uninoculated controls.…”
Section: Methodsmentioning
confidence: 99%
“…Fragaria Xananassa, F. virginiana glauca, day-neutral strawberries, controlled environments, growth models Abstract. Variation in vegetative and reproductive growth patterns leading to summer flowering and fruiting was evaluated in everbearing and in representative Junebearing strawberry (Fragaria Xananassa The major dichotomy in flowering behavior in strawberry, that between Junebearers and everbearers, results from different daylength and temperature requirements for flower bud initiation (FBI) (2,6,7). Day-neutral, relatively temperature-insensitive everbearers initiate flowers from early summer through autumn and may bear several crops per year (9).…”
Section: Methodsmentioning
confidence: 99%
“…yThese are presumably 100/n. meric enzyme in plants, although its inher itance cannot always be inferred by its phenotype due to post-translational modifi cation of the protein, comigrating electromorphs, null alleles, and the presence of interlocus dimers (Arulsekar et al, 1986;Goodman et al, 1980;Cheliak et al, 1985). Phenotypes observed from peach are not eas ily interpreted as dimeric, and several studies have shown that the variation observed can be explained by the segregation of several alleles at one locus, although the origin of all the bands are not always explained (Arul sekar et al, 1986;Durham et al, 1987).…”
mentioning
confidence: 99%